2021
DOI: 10.3390/ijms22115644
|View full text |Cite
|
Sign up to set email alerts
|

Intricate Connections between the Microbiota and Endometriosis

Abstract: Imbalances in gut and reproductive tract microbiota composition, known as dysbiosis, disrupt normal immune function, leading to the elevation of proinflammatory cytokines, compromised immunosurveillance and altered immune cell profiles, all of which may contribute to the pathogenesis of endometriosis. Over time, this immune dysregulation can progress into a chronic state of inflammation, creating an environment conducive to increased adhesion and angiogenesis, which may drive the vicious cycle of endometriosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
126
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(133 citation statements)
references
References 146 publications
(271 reference statements)
3
126
0
4
Order By: Relevance
“…Our systematic review results support the hypothesis that a shortened AGD increases the risk of fecal microbial contamination of the vulva and vagina, resulting in a cervicovaginal microbial imbalance, a subclinical inflammatory response, and then endometriosis (14). Khan et al found elevated levels of Escherichia coli in the menstrual blood of endometriosis patients, suggesting that elevated endotoxin in the peritoneal fluid may promote endometriosis progression via Toll-like receptor (TLR)-4 (38). None of these factors have been definitively shown to have a cause-effect relationship with endometriosis, so it is reasonable to explore additional potential risk factors.…”
Section: Discussionsupporting
confidence: 79%
“…Our systematic review results support the hypothesis that a shortened AGD increases the risk of fecal microbial contamination of the vulva and vagina, resulting in a cervicovaginal microbial imbalance, a subclinical inflammatory response, and then endometriosis (14). Khan et al found elevated levels of Escherichia coli in the menstrual blood of endometriosis patients, suggesting that elevated endotoxin in the peritoneal fluid may promote endometriosis progression via Toll-like receptor (TLR)-4 (38). None of these factors have been definitively shown to have a cause-effect relationship with endometriosis, so it is reasonable to explore additional potential risk factors.…”
Section: Discussionsupporting
confidence: 79%
“…For examples, treating chronic endometritis with antibiotics or uterine lavage has been demonstrated effective to increase conception rates in women of reproductive age [ 76 , 77 ]. On the other hand, because microbes in the gut have huge impacts on female reproductive tract [ 19 , 20 , 21 , 22 , 23 ], diet-induced microbiota remodeling is considered as another possible therapeutic strategy for treating endometriosis. Studies have indicated that women with high intakes of omega-3 unsaturated fatty acids (PUFAs) have a lower risk of developing endometriosis [ 78 , 79 ]; similar dietary benefits have been also shown in mouse studies, resulting in better anti-inflammatory effects and reduced endometriosis formation [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…For examples, gut bacteria has been known to show great impacts on central neuron system, hormone system and other extraintestinal organs of the host, such as the reproductive system [ 19 , 20 ]. Dysbiosis in gut tract has been found to significantly increase estrogen levels in the circulation, which can subsequently stimulate growth of ectopic endometriotic cells and promote inflammatory activity [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the relationships between gut microbial richness, systemic and fecal estrogens, and beta-glucuronidase activity have been demonstrated ( 67 ). Based on these concepts, the term estrobolome was coined to define the gene repertoire of the gut microbiota capable of metabolizing estrogens ( 28 , 76 ). However, just recently, the wider term endobolome was also suggested to address the group of gut microbiota, genes, and pathways involved in the metabolism of any EDC, including the target of this study, the EE 2 ( 29 ).…”
Section: Discussionmentioning
confidence: 99%